2016
DOI: 10.1111/eea.12479
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nitrogen fertilizer on major insect pests and their predators in transgenic Bt rice lines T2A‐1 and T1C‐19

Abstract: Nitrogen is a critical factor for plant development and nitrogen input is one of the important tactics to enhance the development and yield of crops. Nevertheless, nitrogen input could influence the occurrence of insects positively or negatively. Nitrogen is also one of the main elements composing the insecticidal crystal (Cry) protein. Cry protein production could affect nitrogen partitioning in Bt plants and as such nitrogen input may influence insect pest management in transgenic Bt rice, Oryza sativa L. (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It was reported that some of the pesticides have a promotion role in the fecundity and development of BPH, which will accelerate its outbreak of the pest in the field [ 3 , 5 , 6 ]. Moreover, other irrational agronomic practices, such as the irrational use of nitrogen fertilizer, made the control of BPH even more challenging [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that some of the pesticides have a promotion role in the fecundity and development of BPH, which will accelerate its outbreak of the pest in the field [ 3 , 5 , 6 ]. Moreover, other irrational agronomic practices, such as the irrational use of nitrogen fertilizer, made the control of BPH even more challenging [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Bt rice on NTAs including herbivores, predators, parasitoids and detritivores have been studied thoroughly in past 20 years 27 . Recently, much attention has been paid to effects of Bt crops on indirect multi-trophic interactions, whereas few attentions were paid to the combined effects of Bt rice with other biotic or abiotic factors 13 15 , 18 , 19 , 28 31 . Interactions between plants and pathogens on insects are complex.…”
Section: Discussionmentioning
confidence: 99%
“…Bruns and Abel reported that the Bt protein production of two transgenic Bt -transgenic maize lines increased with the augmentation of N fertilizer application 41 . Yang et al found that the contents of Cry2A and Cry1C in Bt rice both increased in the tillering and milking stages with the higher N concentrations applied on rice 42 . Wang et al documented that the Cry1Ab/1Ac content of Bt -SY63 at higher N fertilizer was significantly higher than that without N fertilizer treatment 43 .…”
Section: Discussionmentioning
confidence: 99%